2017
DOI: 10.1016/j.wombi.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The fact and the fiction: A prospective study of internet forum discussions on vaginal breech birth

Abstract: Women search online for information about vaginal breech birth in an attempt to come to a place in their decision-making where they feel comfortable with their birth plan. This study highlights the need for clinicians to provide comprehensive, unbiased information on the risks and benefits of all options for breech birth to facilitate informed decision-making for the woman. This will contribute to improving the woman's confidence in distinguishing between "the fact and the fiction" of breech birth discussions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…To our knowledge, this study is the first to provide a large-scale, big data analysis of online pregnancy forums. While several previous studies have manually examined forum posts relating to specific topics-such as vaginal birth after caesarean section [45], multiple sclerosis [46], and vaginal breech birth [47]-the present study examined 262,238 posts from seven different birth club months, yielding a general topical portrait of all posts. By conducting frequency analyses both overall and within four different timeframes, we were able to highlight dominant topics overall as well as those that were trimester-specific.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this study is the first to provide a large-scale, big data analysis of online pregnancy forums. While several previous studies have manually examined forum posts relating to specific topics-such as vaginal birth after caesarean section [45], multiple sclerosis [46], and vaginal breech birth [47]-the present study examined 262,238 posts from seven different birth club months, yielding a general topical portrait of all posts. By conducting frequency analyses both overall and within four different timeframes, we were able to highlight dominant topics overall as well as those that were trimester-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Its findings support planned VBB within certain clinical parameters. Recent literature has also addressed the previous paucity in qualitative research surrounding term breech birth, with studies considering the experiences of both women and care providers (Walker et al, 2018a(Walker et al, , 2018bCatling et al, 2016aCatling et al, , 2016bPetrovska et al, 2016Petrovska et al, , 2017aPetrovska et al, , 2017bSloman et al, 2016;Watts et al, 2016;Homer et al, 2015;Rosman et al, 2014;Say et al, 2013;Menakaya and Trivedi, 2013;Founds, 2007). However, no research has explored the wider influences involved in parents' decision-making around breech birth.…”
Section: College Of Obstetricians and Gynaecologists 2017)mentioning
confidence: 99%
“…This study explored factors that influence parents' term breech mode of birth decisionmaking within the NHS care model. It involved fathers or partners in addition to mothers, in order to address their limited presence in published research, and in recognition of the role that wider societal influences have been shown to play in women's birth and health-related decisionmaking (Petrovska et al, 2016(Petrovska et al, , 2017a(Petrovska et al, , 2017bDavidson, 2015).…”
Section: College Of Obstetricians and Gynaecologists 2017)mentioning
confidence: 99%
“…The role of clinicians is crucial in providing balanced and nonjudgmental information that is essential for women to support informed decisions about their options for birth when diagnosed with a breech fetus. 9,33,[52][53][54] This may be challenging in the current climate where cesarean birth is seen by many maternity facilities across the world as the safer, default option for birth of a breech fetus. However, the value of womancentered care should be a fundamental element of maternity care, and for this to truly be achieved, the woman should be supported in her decision making for birth.…”
Section: Discussionmentioning
confidence: 99%